Pengaruh Air Rebusan Daun Sirih Hijau Dalam Mempercepat Penyembuhan Luka Perineum Di Klinik Ida Wardani Kabupaten Mandailing Natal Tahun 2022 - Shinta Devi; Basaria Manurung (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
The postpartum period is the condition of a post partum mother who gynecologically returns to her pre-pregnancy state with a recovery time that can last 42 days or 6 weeks and even during the post partum period a mother experiences many physical and psychological changes. This study aims to determine the effect of green betel leaf decoction in accelerating perineal wound healing at the Ida Wardani Clinic, Mandailing Natal District in 2022. This type of research uses a quasi-experimental research method with a post test with control group design. The number of samples used was 20 people. Data analysis technique using paired sample t test. the results obtained from 20 respondents, the results for the value of p = 0.001 means p <0.05, stating that there is a difference in the effectiveness of green betel leaf decoction in accelerating perineal wound healing in the intervention group and the control group. Conclusion: betel leaf boiled water is effective in accelerating healing perineal wounds in postpartum mothers because betel leaf is an alternative plant which has the main component of essential oils consisting of phenol and derivative compounds, so it is very safe for wound healing.